Lex orandi, lex credendi, lex (con)vivendi? – Oriënterende inleiding tot liturgie en etiek - Smit, DJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
Lex orandi, lex credendi, lex (con)vivendi? – Introductory remarks on liturgy and ethics Danie du Toit’s theological career covered three phases: doctoral work on a liturgical- doxological theme in the history of doctrine, teaching systematic theology, and teaching and doing research in ethics. In a remarkable way this corresponds with the popular notion in the history of the church and again today in ecumenical theology, concerning the rule of prayer influencing the rule of faith influencing the rule of life. In Du Toit’s own work he indeed never lost sight of the importance of the worship and spirituality of the church for its faith and doctrine, and he never lost sight of the importance of faith and doctrine for the church’s life and ethics. In characteristic ways, he practiced Christian ethics continuously aware of the church’s traditions of spirituality and doctrine, during a time when many others in the field of ethics increasingly and deliberately moved away from these influences. In this paper, some of the insights of recent developments regarding worship-doctrine-and-life are recounted, in order to provide a framework for further thought on liturgy and life.